A Cooperative Principle: Gricean Maxim Analysis upon a Japanese Light Novel of ‘Shūmatsu Nani Shitemasu Ka? Isogashii Desu Ka? Sukutte Moratte II Desu Ka?” - Vidya Mandarani; Nur Muhammad Ardiansyah (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2018)
This article describes the study of discourse analysis in a specified domain of maxim upon a selected work of Japanese literature, in form of light novel written by Akira Kareno and illustrated by Ue, entitled equals in English as ‘What Do You Do at the End of the World? Are You Busy? Will You Save Us?’. Several objectives are deduced by the researcher in quest of finding the forms of these cooperative principles within the passage. Briefly, maxim itself is a maxim is a compact expression of a general truth or rule of conduct. Also known as a proverb, saying, adage, sentential, and precept, which emphasized the use of formulaic ways of conveying the common wisdom of the people. In our analysis of ‘WorldEnd’ light novel, the varieties of Gricean maxim: maxim of quantity, quality, relevance, and manner, are discussed in order in relation with true meaning discovery behind each cooperative principles properties.